Studying the Magnetic Properties of Compound Complex - Aziz, Abdul Mohammad (Journal of Natural Sciences – Kabul University, 2023)
The magnetic properties of matter arise in two ways from electrons: one is due to the rotational motion of electrons around their axes, and the other is due to the movement of electrons around the nucleus (their orbital motion). Paramagnetic compounds are characterized by unpaired electrons, and their paramagnetic properties are due to the interaction between these electrons and their orbital properties with an external magnetic field. Diamagnetic materials, however, do not exhibit magnetic properties. In transition metals, electrons occupy the d-orbitals, and the magnetic properties of their complexes are closely related to the electron configuration in these orbitals.